AGROTOURISM AS A FORM OF ENTREPRENEURSHIP IN THE ‘BARYCZ VALLEY’ SCENIC PARK - Kurtyka, Izabela (Acta Scientiarum Polonorum. Oeconomia, 2010)
The study presents results of the investigation conducted among 28 owners of agrotouristic farms in the ‘Barycz Valley’ Scenic Park. The aim of the article was to present agrotourism as one of the entrepreneurship’s form, which enlarges income level and farms’ resources usage. Results of the investigation show that agrotourism activity generates the additional income in the Lower Silesia region, which is supplementary in agriculture households’ budgets. All analyzed farms were active and their tillage area ranged from 1 to 10 ha.